Speech Production Analysis of an Autism Character in the Movie “Rain Man” by Barry Levinson (A Psycholinguistic Study) - Sugara, Ria Dewi Hudayani; Alawiyyah, Anisa; Saparianingsih, Ria; Septiani, Arini Nur (Pusat Penerjemah dan Penyunting Universitas Indraprasta PGRI, 2025)
This research aims to find out what are the type of autism experience by Raymond in the movie “Rain Man” and to find out how speech production of autistic experience by Raymond. The method used in this research is qualitative and the object studied is the main actor in the film